Design and Biomedical Applications of Poly(amidoamine)‐Dendrimer‐Based Hybrid Nanoarchitectures. Issue 12 (14th November 2017) - Fan, Yu; Sun, Wenjie; Shi, Xiangyang
Abstract: Dendrimers, especially poly(amidoamine) (PAMAM) dendrimers, possess unique properties such as 3D architecture, monodispersity, highly branched macromolecular characteristics, and tunable terminal functionalities. These properties allow them to be used for controlled synthesis and assembly of hybrid nanoarchitectures with a range of properties suitable for biomedical applications. Here, the recent advances in the design of different PAMAM‐dendrimer‐based hybrid nanoarchitectures for various biomedical applications, in particular for molecular imaging, nonviral gene delivery, and theranostics, are summarized and discussed; future perspectives are also briefly illustrated. Abstract : Recent advances in the design of poly(amidoamine)‐dendrimer‐based hybrid nanoarchitectures for biomedical applications are reviewed. Various dendrimer‐based nanohybrids can be generated through entrapment, stabilization, assembly, complexation, and stepwise grafting. The created nanohybrids are able to be multifunctionalized via versatile dendrimer chemistry to have different biomedical applications including molecular imaging, gene delivery, and theranostics.